2022
DOI: 10.1155/2022/3583603
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Glucose Index for the Diagnosis of Metabolic Syndrome: A Cross-Sectional Study of 298,652 Individuals Receiving a Health Check-Up in China

Abstract: Objective. We herein aim to explore the relationship between the triglyceride-glucose (TyG) index and metabolic syndrome (MS). Methods. We enrolled 298,652 individuals with an average age of 47.08 ± 12.94 years and who underwent health check-ups at the First Affiliated Hospital of Wuhu Wannan Medical College in this cross-sectional study from 2014 to 2016. We enlisted 125,025 women (41.86%) and 173,627 men (58.14%). The survey information included a questionnaire survey, a physical examination, and a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A total of six articles were included in the dose-response analysis ( 29 , 34 , 40 , 42 , 43 , 45 ). After conducting a meta-analysis, the results showed[OR/HR = 1.30 95%CI (1.20, 1.41) P = 0.142] ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of six articles were included in the dose-response analysis ( 29 , 34 , 40 , 42 , 43 , 45 ). After conducting a meta-analysis, the results showed[OR/HR = 1.30 95%CI (1.20, 1.41) P = 0.142] ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, several studies have shown that TyG is a good predictor for metabolism‐related chronic conditions 18,19 . Recently, modified TyG indices combining TyG and body composition indices (body mass index, waist circumference, and waist to height ratio) have emerged and shown higher IR predictive performance than TyG alone 20–24 . Therefore, we hypothesized that TyG and modified TyG indices would be associated with the prevalence of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Recently, modified TyG indices combining TyG and body composition indices (body mass index, waist circumference, and waist to height ratio) have emerged and shown higher IR predictive performance than TyG alone. [20][21][22][23][24] Therefore, we hypothesized that TyG and modified TyG indices would be associated with the prevalence of periodontitis. However, few studies have examined and compared the predictive power of TyG and modified TyG indices for periodontitis.…”
mentioning
confidence: 99%
“…Since MetS components are strongly interconnected with MetS [ 36 ], we investigated whether significantly methylated CpG sites in MetS are linked to other MetS components simultaneously. Therefore, we proceeded to explore the areas of overlap between MetS and its individual components within DMPs and DMRs separately (Fig.…”
Section: Resultsmentioning
confidence: 99%